2007
DOI: 10.1111/j.1475-6773.2006.00683.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Work Hours and Utilization of General Practitioners in Four Canadian Provinces

Abstract: Objective. To assess whether long work hours act as a barrier to accessing general practitioner (GP) services. Data Sources. Secondary data from the 1996/1997 National Population Health Survey (NPHS) and administrative health services utilization data from four Canadian provinces. Study Design. This study was cross-sectional, however, employment variables and GP utilization were reflective of the 12-month period preceding the NPHS interview date. Negative binomial regression was used to model the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…Visiting a physician or CAM provider is time consuming in terms of such things as the time required to make the reservation and for travel, waiting and the consultation itself. Our results are consistent with those of a previous study that showed an inverse association between the number of hours worked and the number of physician visits 20) . With regard to OTC medication and dietary supplement use, given that most OTC medications are only available at pharmacies, whereas dietary supplements are available at supermarkets or over the Internet, longer working hours may act as a greater barrier to accessing OTC medication than dietary supplements.…”
Section: Association Between Hours Worked and Health Resource Utilizasupporting
confidence: 83%
See 1 more Smart Citation
“…Visiting a physician or CAM provider is time consuming in terms of such things as the time required to make the reservation and for travel, waiting and the consultation itself. Our results are consistent with those of a previous study that showed an inverse association between the number of hours worked and the number of physician visits 20) . With regard to OTC medication and dietary supplement use, given that most OTC medications are only available at pharmacies, whereas dietary supplements are available at supermarkets or over the Internet, longer working hours may act as a greater barrier to accessing OTC medication than dietary supplements.…”
Section: Association Between Hours Worked and Health Resource Utilizasupporting
confidence: 83%
“…We speculated that an increase in the number of hours worked may act as a barrier 20) to accessing certain (14) 52 (17) 21 (10) 37 (17) Throat pain/complaints 106 (14) 45 (14) 25 (12) 36 (17) Cough 93 (12) 42 (13) 22 (10) 29 (13) Acute upper respiratory inflammation 73 (10) 28 (9) 22 (10) 23 (11) (762 participants, full-time male Japanese workers, 2003) health resources and that certain resources would be preferred or avoided according to the number of hours worked. Visiting a physician or CAM provider is time consuming in terms of such things as the time required to make the reservation and for travel, waiting and the consultation itself.…”
Section: Association Between Hours Worked and Health Resource Utilizamentioning
confidence: 99%
“…A recent Japanese study found that men working long hours (N 250 per month) made about half as many physician visits as those working fewer (100-200) hours per month (Sato et al, 2011). A 2007 Canadian study found similar results indicating a statistically significant inverse association between patients' long work hours (N 45 h per week) and utilization of general practitioner services (Fell et al, 2007). These findings are consistent with a qualitative study in Canada, which found that work responsibilities and work time were the most commonly mentioned individual barriers to accessing primary care (Wellstood et al, 2006).…”
Section: Introductionmentioning
confidence: 60%
“…Working long hours may limit a woman’s ability to interact with the healthcare system (Fell et al, 2007; Witt et al, 2011), especially during regular office hours. According to a 2009 national survey, only 29% of U.S. primary care practices offered after-hours services whereby patients could see a provider in an non-emergent setting (Schoen et al, 2009).…”
Section: Discussionmentioning
confidence: 99%